Immunomodulation mediated by a herbal syrup containing a standardized Echinacea root extract: a pilot study in healthy human subjects on cytokine gene expression. - Dapas, B; Dall'Acqua, S; Bulla, R; Agostinis, C; Perissutti, B; Invernizzi, S; Grassi, G; Voinovich, D (Phytomedicine, 2014)
In this study, the immunomodulatory effect of a triply standardized Echinacea angustifolia root extract (Polinacea(®)) was evaluated in 10 healthy subjects. Ten ml of syrup containing one hundred mg of extract (corresponding to 4.7 mg of Echinacoside and 8.0mg of a high molecular weight-20,000 Da- polysaccharide) were administered as a herbal syrup once a day for one month. The immunomodulatory effect was evaluated before and after herbal syrup administration evaluating the expression levels of the cytokines IL-2, IL-8, IL-6 and TNF-α. Cytokine expression was studied in lympho-monocytes and in plasma samples measuring the mRNA and protein levels, respectively. The results were analysed by ANOVA and non-parametric Friedman rank sum tests; when possible it was adopted a pair-wise comparisons at different post-treatment times, using the paired t-tests with Holm correction. The correlation between the variations of cytokine plasma levels and the respective mRNA was carried out using a linear regression model. In lympho-monocytes our data indicate the up-regulation of the mRNA levels of IL-2 and IL-8 and the down regulation of the mRNA levels of the pro-inflammatory cytokines TNF-α and IL6. The differential regulation was maximal after 14 days of treatment. IL-2 up-regulation and IL-6 down-regulation were also confirmed at the protein level in plasma. Finally, the up-regulation of the mRNA of IL-2/IL-8 and the down-regulation of IL-6 positively correlated with the protein levels detected in the plasma. In conclusion, this pilot study suggests a relevant role for the standardized Echinacea angustifolia root extract in the control of cytokine expression. This first demonstration of the immuno-modulating activity of Echinacea angustifolia root extract in the healthy subject, supports at least in part the common use of such products as health promoting supplement.
Keywords: Adult; Cytokines; Down-Regulation; Echinacea; Female; Glycosides; Healthy Volunteers; Humans; Immunomodulation; Interleukin-2; Interleukin-6; Interleukin-8; Lymphocytes; Male; Middle Aged; Monocytes; Pilot Projects; Plant Extracts; Plant Roots; Tumor Necrosis Factor-alpha